Challenges in Implementing Scaled Agile Framework (SAFe®) in Global Organizations: A Managerial Perspective - Naznin, Rayhana (My University, 2025)
ABSTRACT: In this era, Agile methodology has had a great impact on project management. Initially, Agile methodology was designed for small companies, but the features like continuous improvement, delivering the best results within a short cycle of time, and leading by example inspired large companies to transform to Agile from traditional methods. The Scaled Agile Framework (SAFe®) has become the most popular model for scaling agile. However, organizations that are already habituated to traditional methods find transformation to the Scaled Agile Framework (SAFe®) challenging for those companies. The main goal of this research is to find out the key challenges during the implementation of the Scaled Agile Framework (SAFe®) in global organizations and the strategies managers use to overcome those challenges. This research follows a qualitative case study to identify the challenges managers face and also focuses on the strategies managers have applied to solve those problems. The author used semi-structured interviews to collect data; all interviewees have working experience with the Scaled Agile Framework (SAFe®), and all of them hold leadership positions. A total of four interviews were conducted, and all interviewees received the research topic and questions before the interview. Data analysis was done by the inductive thematic analysis approach. The result of the study shows that the implementation of the Scaled Agile Framework (SAFe®) in a global organization is not easy; managers are facing many difficulties due to this transformation, but the thing is that they have applied various strategies to overcome those issues. All interviews provided information about challenges and strategies; this study highlights key findings, such as managers face challenges like partial adoption of SAFe® in one organization, resistance to change, communication gaps, and lack of training, and leaders also share effective strategies such as practicing leadership style, improving communications, providing proper training and engaging stakeholders at the early stage of SAFe® transformation. These beneficial insights from managers give instructions for the successful implementation of SAFe®. At the end of the research, suggestions to improve future research are included.
Keywords: fi=Tuotantotalous (tekniikka)|en=Industrial Management and Engineering|; Master's Programme in Industrial Management; Strategic Project Management